Comparison of the immunogenicity and protection against bovine tuberculosis following immunization by BCG-riming and boosting with adenovirus or protein based vaccines - Dean, G; Whelan, A; Clifford, D; Salguero, F; Xing, Z; Gilbert, S; Mcshane, H; Hewinson, R; Vordermeier, M; Villarreal-Ramos, B (2014)
There is a requirement for vaccines or vaccination strategies that confer better protection against TB than the current live attenuated Mycobacterium bovis Bacillus Calmette-Guerin (BCG) vaccine for use in cattle. Boosting with recombinant viral vectors expressing mycobacterial proteins, such as Ag85A, has shown a degree of promise as a strategy for improving on the protection afforded by BCG. Experiments in small animal models have indicated that broadening the immune response to include mycobacterial antigens other than Ag85A, such as Rv0288, induced by boosting with Ad5 constructs has a direct effect on the protection afforded against TB. Here, we compared the immunogenicity and protection against challenge with M. bovis afforded by boosting BCG-vaccinated cattle with a human type 5 (Ad5)-based vaccine expressing the mycobacterial antigens Ag85A (Ad5-85A); or Ag85A, Rv0251, Rv0287 and Rv0288 (Ad5-TBF); or with protein TBF emulsified in adjuvant (Adj-TBF). Boosting with TBF broaden the immune response. The kinetics of Ad5-TBF and Adj-TBF were shown to be different, with effector T cell responses from the latter developing more slowly but being more durable than those induced by Ad5-TBF. No increase in protection compared to BCG alone was afforded by Ad5-TBF or Adj-TBF by gross pathology or bacteriology. Using histopathology, as a novel parameter of protection, we show that boosting BCG vaccinated cattle with Ad5-85A induced significantly better protection than BCG alone. © 2013.